EFFECT OF PLANT EXTRACTS ON BACTERIA FRUIT BLOTCH OF WATERMELON PATHOGEN (Acidovorax citrulli) - P. O, Aji; I. B., Chimbekujwo; H, Nahunnaro; B. A., Tunwari (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Bacterial fruit blotch (BFB) is a significant seed-transmitted disease caused by the gram-negative bacterium, Acidovorax citrulli. This study aimed to determine the effectiveness of plant extracts on Acidovorax citrulli. The research was conducted across nine (9) different communities in three (3) different local governments of Taraba State. Watermelon seeds were germinated and divided into six (6) groups. These groups were then treated with various plant extracts, including garlic oil, Jatropha + garlic oil, Jatropha + Neem oil, Neem oil + garlic oil, Neem oil, as well as a control group, for a period of fourteen (14) weeks. The severity of the infection was measured. In 2021, farms treated with neem oil (7.06%) showed high performance, followed by those treated with Jatropha + neem oil (12.00%), compared to the control group (80.56%) in Ardo Kola. In Tella, farms treated with neem oil (7.92%) and Jatropha + neem oil (13.12%) showed reduced severity. In Wukari, neem oil and Jatropha + neem oil treated farms performed well at 31.96% and 34.68%, respectively, compared to the control at 44.22%. Similar results were observed in the previous year, 2020. The plant extracts suppress the growth of Acidovorax citrulli on the watermelon thereby increases the yield of the watermelon. The extracts can be used in treatment or prevention Bacteria fruit blotch pathogen (Acidovorax citrulli)